Increased placental sFlt-1 but unchanged PlGF expression in late-onset preeclampsia - Laura Ehrlich; Alice Hoeller; Michaela Golic; Florian Herse; Frank H. Perschel; Wolfgang Henrich; Ralf Dechend; Berthold Huppertz; Stefan Verlohren (Hypertension in Pregnancy, 2017)
Objective: To investigate whether differences between late-onset preeclampsia (PE) and intrauterine growth restriction (IUGR) can be explained by differential placental expression patters of sFlt-1, Flt-1, and placental growth factor (PlGF). Methods: Placental tissues and maternal blood samples from seven patients with PE, five IUGR, and seven age-matched controls were studied for mRNA and protein levels as well as protein localization and expression intensity. Results: Placental PlGF mRNA and protein expression were not altered by placental dysfunction while placental villous trophoblast expression intensity of PlGF was increased. Conclusion: High sFlt-1 concentrations may account for diminished maternal serum PlGF levels.